Multi-Keyword Privacy Security Protected Search Through Encrypted Data On Cloud Storage - et. al., Anwar Basha H, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Through the advancement of cloud storage, data providers are allowed to outsource their complicated data processing processes with considerable versatility and economic benefits since local locations to the private, public cloud. However, confidential data must be secured before outsourcing in order for data to be safe, which obsolescent common usage of data relying on plaintext search. Therefore, it is incredibly necessary to allow a secure cloud data search service Given the vast number of web users and cloud records, in order to be applicable to such keywords, several keywords should be acknowledged in the search request and return records. The searchable encryption-based research specializes in search of a particular keyword or in boolean keywords, seldom processing the outcomes of pursuit. For the very first time, the problem of protecting the privacy of multi - keyword search for encrypted data in cloud storage is described as well as solved in this article. For such a safe cloud data usage scheme, we series a series of strict privacy criteria. We pick from the different multi-keyword semantics the effective "coordinate matching" similarity test, i.e. as various matches as likely, in order to catch the importance of the data papers to the search. We can use "inner product similitude" to test this resemblance attribute quantitatively. Initial, on the basis of stable internal commodity estimation and then, in two separate Vulnerability Models, we suggest a simple concept for the MRSE to reach multiple rigorous data protection standards. We expand these two frameworks to help further search terminology to improve our user experience for the data search service. Examination of data security and assurance of performance of suggested systems shall be carried out in-depth. Experiments in the real-world data set indicate that plans for numerical and connectivity structures effectively add small overheads.